2017
DOI: 10.1016/j.biopen.2017.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Purified horse milk exosomes contain an unpredictable small number of major proteins

Abstract: Exosomes are 40–100 nm nanovesicles containing RNA and different proteins. Exosomes containing proteins, lipids, mRNAs, and microRNAs are important in intracellular communication and immune function. Exosomes from different sources are usually obtained by combination of centrifugation and ultracentrifugation and according to published data can contain from a few dozens to thousands of different proteins. Crude exosome preparations from milk of eighteen horses were obtained for the first time using several stan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 49 publications
2
48
0
4
Order By: Relevance
“…As mentioned above, exosome preparations obtained from different biological fluids using different types of centrifugation and ultracentrifugation can contain according to from a few dozen to several thousands of different proteins. However, as has been shown recently after additional purification of exosomes from coprecipitating proteins and their complexes by gel filtration, they contain no more than 10–12 major proteins ().…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…As mentioned above, exosome preparations obtained from different biological fluids using different types of centrifugation and ultracentrifugation can contain according to from a few dozen to several thousands of different proteins. However, as has been shown recently after additional purification of exosomes from coprecipitating proteins and their complexes by gel filtration, they contain no more than 10–12 major proteins ().…”
Section: Resultsmentioning
confidence: 85%
“…Our data shows that ferritin is not a part of exosomes, and should be considered as impurity even in preparations purified on anti‐CD81 Sepharose. Thus, there is a relatively small number of major proteins (Table ) in purified exosomes from human placenta, similar to exosomes from mare's milk .…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Stable multiprotein complex samples were applied for 1 minute for adsorption on a copper grid covered by formvar film stabilized with carbon and used for negative contrast according to Sedykh et al The grid was placed on a drop of 0.5% solution of uranyl acetate or 2% solution of phosphotungstic acid (5‐10 s); the excess of liquid was removed with filter paper. The grid was examined using a transmission electron microscope Jem1400 (Jeol, Japan), and images were obtained using a Veleta digital camera.…”
Section: Methodsmentioning
confidence: 99%
“…In the recent years, several studies revealed that human, bovine, pig and rat milk, as well as other biological fluids, contained miRNAs [82,83]. In particular, the miRNA microarray analyses of bovine milk revealed the presence of 79 and 91 miRNAs in the exosomes milk and in the supernatant whey derivatives, respectively [84]. Exosomes are naturally 30-100 nm nanovescicles containing different biomolecules including nucleic acids such as miRNAs and other ncRNAs, secreted into the extracellular liquids by different types of cells [85].…”
Section: Mirnas and Evolutionmentioning
confidence: 99%